Low prevalence of stds among sex professionals in Manacapuru Country, interland of the State of Amazonas, Brazil - Benzaken, Adele S.; Garcia, Enrique G.; Sardinha, José Carlos G.; Pedrosa, Valderiza L.; Loblein, Osminda (Brazilian Journal of Sexually Transmitted Diseases, 2002)
A random sample of 144 women were selected from what is estimated as being a total of 500 sex professionals distributed among 30 prostitution points in the municipality of Manacapuru (confidence level 95%. minimum prevalence for STD 5% and an acceptable error of 2%). taking the points as being grouped. A total of 147 professionals participated in the study during the year 2(XX). Each of the sample’s sex professionals responded to a questionnaire and underwent a gynecological examination where samples were taken for study of gonococcal infection (culture), chlamydia infection (IFI), syphilis (VDRL). trichomoniasis, Candida and bacterial vaginosis infections (amine test. Gram stain and microscopy). Testing for HIV antibodies was also offered. The prevalence rates found for gonococcal infection, chlamydia infection, trichomoniasis, syphilis. HIV, HPV and genital herpes were 16.3%; 7.5%>; 23.1%; 0.68% ; 0.0% ; 6.1% and 1.4% respectively. Vaginal discharge syndrome was present in 98%, pelvic pain 28.6% and cervical discharge 12.9%.78 women (53%) performed VDRL and reactive serum prevalence found was 3.8%. The global prevalence of STD (etiologically diagnosed) was 42.9%. Curable STD (bacterial vaginosis and trichomoniasis) represented the most frequent problem (39.5%), viral infections were present in 7.5%. The prevalence of asymptomatic STD in women was 33.3% (10/30) and 47% (55/117) were symptomatic (p=0.17). The prevalence of HIV. syphilis and chlamydial infection can be considered very low. whilst the levels for gonococcal and trichomoniasis infections are comparable to average international standards. Curable STD’s were more prevalent in the younger age group, with the exception of chlamydia infections which were similar throughout the group. No differences were noted in the prevalence of gonococcal and chlamydia infections in symptomatic and asymptomatic women.